Pengaruh Modal Kerja Dan Arus Kas Terhadap Laba Bersih Pada PT Mayora Indah TBK Periode 2013-2022 - Ardi Bachtiar; Indri Kharisma; Ananda Hadistia (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effect of Working Capital and Cash Flow on Net Profit at PT. Mayora Indah, Tbk. The research method used in this study uses a descriptive quantitative method using secondary data obtained from the financial statements of PT. Mayora Indah, Tbk. 2013-2022. The statistical data analysis method used is Multiple Linear Regression and the Classical Assumption Test is carried out first, in addition to using the Hypothesis Test (T Test) and Simultaneous Test (F Test) statistical data processing is carried out using SPSS data processing software. From the multiple linear regression test, the results show that partially Working Capital has a significant effect partially on the Net Profit Level, the t-value is 3.259> 2.364 and the significance value is 0.014 <0.05. Cash Turnover does not have a significant effect on Net Profit obtained from the results of the calculated t value of 1.262 < 2.364 and a significance value of 0.247 > 0.05. Simultaneously, Working Capital and Cash Flow have a significant effect on Net Profit. This result is obtained from the calculated f value of 5.374 > ftable 4.74 and a significance value of 0.039 < 0.05. The Independent Variables of Working Capital and Cash Flow explain that there is an influence on the Net Profit Level of 60.6% while the remaining 39.4% is influenced by other variables not examined in this paper.